2020
DOI: 10.1002/ece3.6707
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of egg size and appearance on egg recognition and rejection response by Oriental reed warblers

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 60 publications
1
8
1
Order By: Relevance
“…In this study, Oriental Reed Warblers, as one of the most common hosts of cuckoos, have a nearly 100% rejection rate for non-mimetic eggs, similar to the population in northeastern China, which rejected both blue (n = 15) and white (n = 24) model eggs at a rate of 100% (Wang et al 2021) and the Japanese population (94%, n = 33; Lotem et al 1995), suggesting that the Oriental Reed Warbler possesses an extremely strong egg recognition ability. However, egg rejection of another population of Oriental Reed Warblers (Li et al 2016(Li et al , 2020 was slightly lower than that of this population, possibly because the material and size of experimental eggs used may influence on the host's completion of egg rejection (Roncalli et al 2017;Li et al 2020).…”
Section: Discussionmentioning
confidence: 69%
“…In this study, Oriental Reed Warblers, as one of the most common hosts of cuckoos, have a nearly 100% rejection rate for non-mimetic eggs, similar to the population in northeastern China, which rejected both blue (n = 15) and white (n = 24) model eggs at a rate of 100% (Wang et al 2021) and the Japanese population (94%, n = 33; Lotem et al 1995), suggesting that the Oriental Reed Warbler possesses an extremely strong egg recognition ability. However, egg rejection of another population of Oriental Reed Warblers (Li et al 2016(Li et al , 2020 was slightly lower than that of this population, possibly because the material and size of experimental eggs used may influence on the host's completion of egg rejection (Roncalli et al 2017;Li et al 2020).…”
Section: Discussionmentioning
confidence: 69%
“…In general, egg color and maculation are the main cues used by bird hosts to recognize alien eggs, 28,29 but their relative contributions to the recognition process varies among hosts. 5,31 In this study, increasing the maculation density had no effect on egg recognition, while changing the egg ground color significantly increased the rejection rate.…”
Section: Discussionmentioning
confidence: 99%
“…4,[24][25][26] Among the recognition cues, egg color and maculation are most important in the process of host egg recognition. [27][28][29][30] Rothstein 11 studied the relative effects of egg color, maculation, and size on egg recognition in the American robin (Turdus migratorius) and found that the host rejects model eggs differing in at least two characteristics from its own eggs. Luro et al 29 replicated this study, confirmed most of the original findings and showed that egg size is less predictive than other characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…We selected blue color for the experimental eggs because this is a conspicuous color unlike the egg color of the tested hosts. In addition, blue model eggs better mimic the ultraviolet part of the spectrum of host eggs and appear more likely to the green‐blue background of the natural eggs of Acrocephalus warblers than, for example, brown spotted eggs (Li et al, 2020). We did not use a control (simulated debris) to test whether the observed egg rejection rate was a result of the nest sanitation behavior of hosts or a defense against brood parasitism since hosts including the great reed warbler and Oriental reed warbler generally consider artificial egg‐shaped objects to be eggs (see also Honza & Moskát, 2008; Li et al, 2020; Ma & Liang, 2021; Moskát et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…We selected blue color for the experimental eggs because this is a conspicuous color unlike the egg color of the tested hosts. In addition, blue model eggs better mimic the ultraviolet part of the spectrum of host eggs and appear more likely to the green-blue background of the natural eggs of Acrocephalus warblers than, for example, brown spotted eggs (Li et al, 2020).…”
Section: Study Site and General Field Proceduresmentioning
confidence: 99%